KADAR VITAMIN C DAN ANTIOKSIDAN PADA DONAT BOMBOLONI TEPUNG DAUN PANDAN DENGAN ISI ABON IKAN PATIN - Demitri, Athira; Harahap, Lutfi Henderlan; Jairani, Eka Nenni (LPPM Institut Kesehatan Helvetia, 2024)
Background; Bomboloni donuts are one of the products that are liked by the public, especially children, so innovation can be done, by using pandan leaf flour and filling with patin fish floss. Pandan leaves have bioactive compounds such as vitamin C and antioxidants, which can increase the nutritional value of food products. Patin fish floss is chosen as a filling because it contains 18 grams of protein in 100 grams of fish. Objectives; To analyze the levels of vitamin C and antioxidants in pandan leaf flour bomboloni donuts filled with patin fish floss. Material and Method; This type of research was experimental, with three product formulations (F1, F2, F3). Making bomboloni donuts from pandan leaf flour with patin fish floss filling at the Food Technology Laboratory Institut Kesehatan Helvetia and examining vitamin C and antioxidant levels at the Politeknik Teknologi Kimia Industri Laboratory. The weight of the research sample when examining vitamin C and antioxidant levels with 30 grams of donut skin and 20 grams of patin fish floss filling. Results; Vitamin C levels in F1 (8.37 mg/gram), F2 (10.40 mg/gram), and F3 (9.10 mg/gram). Antioxidants in each formulation in IC50 PPM values in F1 (31.47), F2 (30.11), and F3 (34.81) Conclusion; F2 has higher vitamin C levels compared to F1 and F3. Higher antioxidants in F3 treatment were due to the addition of 15% pandan leaf flour, compared to F1 at 5% and F2 at 10%.